Study of a Large Intraorbital Wooden Foreign Body Perforating the Lateral Orbital Wall of Left Eye in a Child: A Clinical Approach - Maheshwari, Dhwani; Solanki, Arpita (New Frontiers in Medicine and Medical Research Vol. 11, 2021)
Children in India are most susceptible to injury from wooden objects, spear, ball etc., therefore there should be awareness regarding precautions to be taken as well as management of such injuries. Intraorbital foreign bodies in children are difficult to detect. Organic and non organic intraorbital foreign bodies behave differently, they can have varied prognosis. This article entails management of such cases. A 6-year-old girl came to our clinic with a history of having a foreign body caught in her eye.A CT scan indicated a hypodensity implanted in the left lateral orbital wall, abutting and compressing the globe of the left eye with a displaced comminuted fracture, according to the report. We performed an operation to remove a foreign body from the eye, which was extremely difficult and precise due to the sensitivity of the situation.On the day after surgery, the CT scan revealed no foreign bodies, chemosis, and full ocular mobility.The cornea was clear, the anterior chamber was quiet, and the pupil was normal. A dilated fundoscopy revealed no abnormalities.